Search for additional scalar bosons within the Inert Doublet Model in a final state with two leptons at the FCC-ee - Anubha Bal; Edward Curtis; Anne-Marie Magnan; Benedikt Maier; Tania Robens; Nicholas Wardle (European Physical Journal C: Particles and Fields)
Abstract We present a search for new scalar bosons predicted by the Inert Doublet Model at an $$e^+e^-$$ e + e - machine with centre-of-mass energies $$\sqrt{s} $$ s of 240 and 365 $$\text {G}\text {eV}$$ G . Within this model, four additional scalar bosons ( $$H,\, A,\, H^+$$ H , A , H + and $$H^-$$ H - ) are predicted. Due to an additional symmetry, the lightest new scalar, here chosen to be H, is stable and provides an adequate dark matter candidate. The search for pair production of the new scalars is investigated in final states with two electrons or two muons, in the context of the future circular collider proposal, FCC-ee. Building on previous studies in the context of the CLIC proposal, this analysis extends the search to detector-level objects, using a parametric neural network to enhance the signal contributions over the Standard Model backgrounds, and sets projected exclusion and discovery contours in the $$M_A-M_H$$ M A - M H vs. $$M_H$$ M H plane. With a total integrated luminosity of 10.8 (2.7)  $$\,\hbox {ab}^{-1}$$ ab - 1 for $$\sqrt{s} =$$ s = 240 (365)  $$\text {G}\text {eV}$$ G , the discovery reach for the model goes up to $$M_H$$ M H $$= 108\,(157)\,\text {G}\text {eV}$$ = 108 ( 157 ) G for $$M_A-M_H$$ M A - M H $$=15$$ = 15   $$\text {G}\text {eV}$$ G at $$\sqrt{s} =$$ s = 240 (365)  $$\text {G}\text {eV}$$ G . For exclusion, almost the entire phase-space available in the $$M_A-M_H$$ M A - M H vs. $$M_H$$ M H plane is expected to be ruled out at 95% CL, reaching up to $$M_H$$ M H $$=110\,(165)$$ = 110 ( 165 )   $$\text {G}\text {eV}$$ G .